Kampanye Moderasi Beragama di Ruang Digital Indonesia - Robeet Thadi (Institut Agama Islam Negeri Bengkulu, 2022)
Religious moderation is a trending conversation in the digital space, this article aims to explain the concept of religious moderation, religious topics, forms of campaigns, and strategies for campaigning for religious moderation in Indonesia's digital space. This article uses a qualitative approach to the liberary research method. The results of the study show that, in terms of the concept of moderation, religion is a middle attitude, not secular and not religious. The religious topic of religious moderation from the Google search engine page uses the keywords